Propiedades de resistencia de una pulpa kraft de pino mezclada con médula del bagazo de caña de azúcar - Rutiaga Quiñones, José Guadalupe; Anzaldo Hernández, José; Vargas Radillo, José de Jesús; Sanjuán Dueñas, Rubén (Instituto de Ecología, A.C., 2016)
Bleached kraft pulp of Pinus douglasiana was mixed with bleached pith of sugarcane bagasse and handsheets were made according to TAPPI methods. A factorial design experiment (3x5) was applied for the evaluation of the effects of pith on the breaking length and the tear index of handsheets (factor A = refining degree pulp: 12 °SR, 30 °SR and 60 °SR; factor B = quantity of pith: 0%, 10%, 20%, 30% and 40%). The results showed that the pith helped to increase the breaking length, especially in pulp with 12 °SR and 30 °SR. Statistical differences for both response variables between the pulp with 12 °SR and the pulp refined to 30 °SR and 60 °SR were found, whereas, statistically, the results for the two pulps refined to 30 °SR and 60 were similar.